Smart Trash Can with Odor and Humidity Detection Using Arduino: Tempat Sampah Cerdas dengan Fitur Deteksi Bau dan Kelembapan Menggunakan Arduino - Ferdianto; Shazana Dhiya Ayuni (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Smart waste management technologies are increasingly developed to support environmental cleanliness and user convenience in daily activities. Specific Background: Previous smart trash can systems commonly focused on automatic lid control and waste level monitoring using sensor-based automation. Knowledge Gap: Limited studies have integrated odor detection and humidity monitoring into an automatic trash can system to improve household waste handling and environmental comfort. Aims: This study aimed to develop a smart trash can system capable of automatic opening and closing while detecting unpleasant odor and humidity conditions using Arduino Uno, HC-SR04, MQ-135, and DHT11 sensors. Results: The developed system successfully performed automatic lid movement through a servo motor when objects were detected at distances greater than 40 cm by the HC-SR04 sensor. The MQ-135 sensor detected unpleasant odor conditions above 50 PPM, causing the automatic opening mechanism to stop operating, while the DHT11 sensor activated a buzzer alarm when humidity exceeded 80%. Novelty: This research integrates distance detection, odor sensing, and humidity monitoring within a single smart trash can prototype using multiple sensor configurations and Arduino-based control. Implications: The proposed system contributes to environmentally oriented household waste management by providing automated operation and monitoring features that support cleaner and more comfortable surroundings.Highlights: Automated lid operation responded to object detection beyond 40 cm using ultrasonic sensing. Ammonia concentration above 50 PPM stopped servo activation during waste disposal conditions. Humidity monitoring triggered an audible alarm when moisture levels exceeded 80%. Keywords: Arduino Uno; Smart Trash Can; MQ-135 Sensor; DHT11 Sensor; Waste Management